Ultra-small Hysteresis IGZO Thin-Film Transistors with Room-Temperature Sputtered SiO2 as Dielectric Layer - Fangfei Han; Zheng Lu; Luan Fu; Lulu Du; Xiaohui Shi (Journal of Applied Science and Engineering)
A sputtered silicon dioxide dielectric is prepared for fabrication of indium gallium zinc oxide (IGZO) thin-film transistors (TFTs). We analyzed the dependence of device characteristics on gate voltage range. Clockwise hysteresis occurs at a low gate voltage ( Vgs ≤ 3 V) due to oxide traps near the SiO2/IGZO interface. At higher gate voltage ( Vgs = 5 V) a second, hysteresis collapse appears, which can be attributed to the coexistence of electron trapping and ion migration with a compatible and the opposite contributions to the hysteresis. Due to the dominant ion migration, hysteresis inversion (clockwise to anti-clockwise) appears at Vgs = 7 V. At Vgs = 10 V, devices performance degrades significantly, which may be ascribed to the electrochemical reaction. Further, a bias stress measurement indicates that the devices work effectively under a wide range Vgs of 1 ∼ 7 V